Synthesis and photo-/electro-catalytic properties of a 3-D supramolecular framework based on [HxAs2Mo6O26](6−x)− and Cu-diz complexes. Issue 3 (1st February 2018) - Cong, Bowen; Su, Zhanhua; Zhao, Zhifeng; Zhao, Wenqi; Ma, Xiujuan
Abstract: Herein, an arsenomolybdate, Cu(diz)4 (H2 O)2 [Cu(diz)2 (H2 O)2 2 As2 Mo6 O26 ]·2H2 O (diz = 1, 2-diazole) (1 ), has been synthesized under hydrothermal conditions and characterized by single-crystal X-ray diffraction, elemental analysis, IR, TG, XPS, PXRD, and UV–Vis-NIR. The Cu-diz complexes link the [As2 Mo6 O26 ] 6− polyoxoanions, forming a 1-D infinite chain. The 2-D layer is constructed from 1-D chains through hydrogen bonds. Adjacent layers and free Cu(diz)4 (H2 O)2 complexes are fused through hydrogen bonding to form a 3-D topological framework with symbol of 4 14 ·6 10 ·8 4 4 2 . Compound1 exhibits luminescence at room temperature, excellent degradation activity for four different organic dyes (RhB, MB, MO, and AP) under UV irradiation. The photocatalytic mechanism of1 is discussed in detail. Furthermore, the electrocatalytic activity of1 toward hydrogen peroxide has also been studied. Abstract :